Correlation Analysis on Social Psychological Adjustment, Sports Cultural Products Consumption, and Sports Cultural Industry Development - Cuibi Yang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The society today advocates the prosperity of cultural undertakings and cultural industries, and pursues the enhancement of cultural soft power. Sports development is closely connected with economic development. The complementarity between the two is the inevitable trend of our society. However, there are relatively few studies on sports cultural products consumption (SCPC) and sports cultural industry development (SCID). Besides, the influence of social psychological adjustment (SPA) on the entire sports cultural industry is largely overlooked. Therefore, this paper explores the correlations between SPA, SCPC, and SCID. Firstly, the relationship between SCPC and SCID was modeled, and the action mechanism of SCPC on SCID was detailed. Next, the dynamic correlation between SCPC and SCID was analyzed. After that, SPA was introduced to discuss the associations between SPA, SCPC, and SCID from the perspective of correlations. The Augment Dickey-Fuller (ADF) unit root test and Johansen cointegration test were carried out to verify whether SPA, SCPC, and SCID are stationary, and have long-term equilibrium relationships in the long run. Finally, experiments were carried out to estimate the correlations between the three, using three-stage least squares (LS) method, and obtain the results of ADF and Johansen tests. The study on the interaction mechanism between SPA, SCPC, and SCID clarifies their interactive paths, and helps policymakers to roll out favorable policies on the following issues: designing institutional incentives of SCPC, enhancing the fundamental role of SCPC in SCID, and promoting the high-quality regional economy development under SPA.